Corporate Social Responsibility: Dimensions and Challenges in Bangladesh - Hossen , Mohammad Awal (Global Disclosure of Economics and Business, 2016)
This paper aims at exploring the dimensions and challenges of corporate social responsibility (CSR) in the context of Bangladesh, taking Carroll’s CSR Pyramid as a conceptual framework for explicative analysis. Carroll’s CSR Pyramid is by far the most well-known framework of CSR, which gives relative importance to economic, legal, ethical and discretionary (philanthropic) obligations of corporations towards society. As the countries differ in their economical, social and political conditions around the globe, the dimensions of CSR and the challenges in executing CSR initiatives also differ. This study found that the dimensions currently in practice and applicable to Bangladesh do not follow the same order as proposed by Carroll in the context of developed countries. It is suggested that the relative priorities of CSR in case of Bangladesh are to be in the following order: economic, philanthropic, environmental, legal and ethical responsibilities. Finally, some suggestions for successful execution of CSR initiatives are also given.